Investigating tumor immunogenicity in breast cancer: deciphering the tumor immune response to enhance therapeutic approaches - Naji, Oumayma; Ghouzlani, Amina; Rafii, Soumaya; Sadiqi, Rizwan ullah; Kone, Abdou-samad; Harmak, Zakia; Choukri, Khalil; Kandoussi, Sarah; Karkouri, Mehdi; Badou, Abdallah (Frontiers in Immunology, 2024)
The interplay between immune cells and malignant cells represents an essential chapter in the eradication of breast cancer. This widely distributed and diverse form of cancer represents a major threat to women worldwide. The incidence of breast cancer is related to several risk factors, notably genetic predisposition and family antecedents. Despite progress in treatment modalities varying from surgery and chemotherapy to radiotherapy and targeted therapies, persistently high rates of recurrence, metastasis, and treatment resistance underscore the urgent need for new therapeutic approaches.Immunotherapy has gained considerable ground in the treatment of breast cancer, as it takes advantage of the complex interactions within the tumor microenvironment. This dynamic interplay between immune and tumor cells has become a key point of focus in immunological research. This study investigates the role of various cancer markers, such as neoantigens and immune regulatory genes, in the diagnosis and treatment of breast tumors. Moreover, it explores the future potential of immune checkpoint inhibitors as therapeutically effective agents, as well as the challenges that prevent their efficacy, in particular tumorinduced immunosuppression and the difficulty of achieving tumor specificity.